2015
DOI: 10.1186/s13024-015-0059-y
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of novel CSF biomarkers for neurodegeneration and their validation by a high-throughput multiplexed targeted proteomic assay

Abstract: BackgroundCurrently there are no effective treatments for many neurodegenerative diseases. Reliable biomarkers for identifying and stratifying these diseases will be important in the development of future novel therapies. Lewy Body Dementia (LBD) is considered an under diagnosed form of dementia for which markers are needed to discriminate LBD from other forms of dementia such as Alzheimer’s Disease (AD). This work describes a Label-Free proteomic profiling analysis of cerebral spinal fluid (CSF) from non-neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 50 publications
7
110
1
Order By: Relevance
“…More recently, our group has shown that in AD and in mild cognitive impairment (MCI) patients, TTR protein levels are decreased (10) compared with age-matched controls, which is in agreement with a previous observation of lower levels of CSF TTR in AD patients (11). Moreover, TTR levels in the CSF were found to be negatively correlated with formation of senile plaques (12) and disease progression (13), and positively correlated with Aβ 42 CSF levels in AD patients (14). Thus it is hypothesized that before Aβ deposition, diminishment of TTR is responsible for increased levels of Aβ 42 , consequently promoting its deposition, and finally, with disease establishment, CSF Aβ 42 levels decrease due to sequestration in senile plaques.…”
supporting
confidence: 87%
“…More recently, our group has shown that in AD and in mild cognitive impairment (MCI) patients, TTR protein levels are decreased (10) compared with age-matched controls, which is in agreement with a previous observation of lower levels of CSF TTR in AD patients (11). Moreover, TTR levels in the CSF were found to be negatively correlated with formation of senile plaques (12) and disease progression (13), and positively correlated with Aβ 42 CSF levels in AD patients (14). Thus it is hypothesized that before Aβ deposition, diminishment of TTR is responsible for increased levels of Aβ 42 , consequently promoting its deposition, and finally, with disease establishment, CSF Aβ 42 levels decrease due to sequestration in senile plaques.…”
supporting
confidence: 87%
“…Separate from the metabolic pathway, we observed increased levels of M4 proteins osteopontin (SPP1), dickkopf-related protein 3 (DKK3), and CD44. SPP1 has been nominated as an AD CSF biomarker in previous studies [106][107][108][109] . SPP1 is known to be involved in tissue repair 110 , and promotes phagocytosis of amyloid-β and an anti-inflammatory microglial phenotype 111,112 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies for AD biomarkers have demonstrated conflicting results with respect to whether apoE levels in CSF and plasma are reduced in AD patients compared to normal individuals [9598]. Nonetheless, there are numerous animal studies evaluating the therapeutic potential of compounds that increase brain apoE levels [99115].…”
Section: Apoe-targeted Therapy For Admentioning
confidence: 99%